Stratification of Patients with Burning Mouth Syndrome in the Croatian Population: A Single-Center Cross-Sectional Study - Ana Glavina; Ana Trlaja; Dinko Martinović; Antonija Tadin; Liborija Lugović-Mihić (NeuroSci, 2025)
The objective of the study was to determine the relationship between burning, xerostomia, dysgeusia and other subjective symptoms in patients with burning mouth syndrome (BMS). This cross-sectional study was conducted at the Dental Polyclinic Split, Split, Croatia. A total of 71 patients with BMS, i.e., 60 women and 11 men, were included in the study. The patients were divided into four subgroups: burning (B), burning and xerostomia (BX), burning and dysgeusia (BD), burning, xerostomia and dysgeusia (BXD). The following data were collected from all patients: sociodemographic status, comorbidities, medications, characteristics of the burning, presence of other subjective symptoms, topography of the burning. The majority of patients with BMS were women (86.0%) with an average age of about 65 years. Gastrointestinal diseases were the most common comorbidity (48.35%), and the most commonly used medications were proton pump inhibitors (PPIs) (29.8%). In the largest number of patients (N = 34), the burning symptom worsened in the evening hours (p = 0.059). The majority of BMS patients suffered from burning symptoms that occurred continuously (N = 54, 75.13%) and from an improvement (reduction/cessation) of symptoms during meals (N = 54, 76.65%). Of the other subjective symptoms, changes in the morphology of the tongue (10.6%) and a feeling of swelling (9.1%) were the most common. The tongue was the most common localization (67.35%). The multivariable logistic regression analysis showed a statistically significant effect of female gender (p = 0.049) as a potential positive predictor in subgroup B. The sociodemographic and medical data collected cannot explain the different occurrence of symptoms in the four subgroups of patients with BMS.